Efficacy of the 'Five-Needle' method for pancreatojejunostomy in laparoscopic pancreaticoduodenectomy: an observational study - Wang, Zheng-Feng; Zhang, Bo; Xu, Hao; Zhou, Wen-Ce (Frontiers in Oncology, 2024)
The aim of thethis study iswas to explore the clinical efficacy and adverse reactions of thethis new surgical method, and to provide a scientific reference for promoting this new surgical method in the future.Methods: A single -centre center observational study was conductconducted to evaluate the safety and practicality of the 'Five-Needle'five-needle method for pancreatojejunostomy in LPD surgeries. ClinicalThe clinical data of 78 patients who were diagnosed with periampullary malignancies and treated withunderwent LPD waswere collected from the 1 st ,of August, 2020, to the 31 st of June, 2023 at Lanzhou University First Hospital. 43Forty-three patients were treated with the 'Five-Needle' method (test groups), and 35 patients were treated with the 'Duct-to-Mucosa' method (control group) infor pancreatojejunostomy, respectively. These two methods wereare the most commonly used and most skilledhighly preferred pancreato-intestinalpancreatointestinal anastomosis methodmethods worldwide. The primary outcomesoutcome was pancreatic fistula, and the incidence of which was were compared in between the two groups.Result: Results: The incidence of pancreatic fistula in the 'Five-Needle'five-needle method group and and 'Duct-to-Mucosa' the duct-to-mucosa method group was no statistical significancenot significantly different (25.6% vs. 28.6%, p=0.767). Additionally, there were no significant differences between the two groups in terms of intraoperative blood loss (Z=-1.330, p=0.183), postoperative haeemorrhage rates (p=0.998), length of postoperative hospital stay (Z=-0.714, p=0.475), bile leakleakage rate (p=0.745), andor perioperative mortality rate (p=0.999). However, the operative time for in the 'Five-Needle' method group was significantly shorter than that for in the 'Duct-to-Mucosa' method group (270±170 mins vs. 300±210 mins, Z=-2.336, p=0.019). Further analysis showedrevealed that in patients with pancreatic ducts smaller than 3 mm, the incidence rate of pancreatic fistula was lower infor the 'Five-Needle''Five-Needle' method compared tothan for the p=0.007).The 'Five-Needle'five-needle method is safe and efficient of for pancreatojejunostomy is a safe and efficient surgical method in LPD,, and is particularly suitable for anastomosis in non-dilatednondilated pancreatic ducts. It is a promising, valuable, and recommendable surgical method worthy of wider adoption.Laparoscopic Pancreaticoduodenectomy (LPD), ' Five-Needle ' method, 'Duct-to-Mucosa' method ， pancreatic fistula ， pancreaticoduodenectomy (LPD), five-needle method, duct-to-mucosa method, pancreatic fistula, operative time